Analysis of the Operating Capacity of Chinese New Energy Electric Vehicles Industry: Taking NIO as an Example - Xuanjian Huang; Xin Zhang (Journal of Frontier in Economic and Management Research, 2025)
Spurred by the global climate crisis, nations worldwide are accelerating energy-structure adjustments and promoting the low-carbon transformation of the transport sector through policy incentives. Concurrently, the deep integration of digital technologies and artificial intelligence is reshaping the automotive landscape, driving the joint evolution of electric powertrains and intelligent-driving capabilities and laying the technological foundation for smart mobility solutions. Amid this shift, an emerging cohort of next-generation automakers has entered the market. This study focuses on NIO Inc. as a representative firm within the global new-energy-vehicle (NEV) segment. Based on the operational capacity theory, study selects three key operational ratios: accounts receivable turnover, inventory turnover, and total asset turnover. Its primary objectives are to evaluate NIO’s operational efficiency against industry benchmarks by checking NIO’s annual financial report data from 2019 to 2023, and to propose actionable recommendations for the operational challenges identified. The study found that the accounts receivable turnover and inventory turnover of NIO fluctuated significantly, while the total asset turnover was relatively low. To address that, three improvement suggestions were proposed: refining credit management, optimizing inventory management, and enhancing asset utilization. It is hoped that these suggestions would provide a reference for other NEV enterprises and contribute to better promoting development of the industry.